Malaria and typhoid fever among patients presenting with febrile illnesses in Ga West Municipality, Ghana. - Tanko Rufai; Enoch Aninagyei; Kwadwo Owusu Akuffo; Christian Teye-Muno Ayin; Priscillia Nortey; Reginald Quansah; Francis Samuel Cudjoe; Ernest Tei-Maya; Isaiah Osei Duah Junior; Anthony Danso-Appiah (PLoS ONE, 2023)
Background Clinicians in areas where malaria and typhoid fever are co-endemic often treat infected patients irrationally, which may lead to the emergence of drug resistance and extra cost to patients. This study determined the proportion of febrile conditions attributable to either malaria and/or typhoid fever and the susceptibility patterns of Salmonella spp. isolates to commonly used antimicrobial agents in Ghana. Methods One hundred and fifty-seven (157) febrile patients attending the Ga West Municipal Hospital, Ghana, from February to May 2017 were sampled. Blood samples were collected for cultivation of pathogenic bacteria and the susceptibility of the Salmonella isolates to antimicrobial agents was performed using the Kirby-Bauer disk diffusion method with antibiotic discs on Müller Hinton agar plates. For each sample, conventional Widal test for the detection of Salmonella spp was done as well as blood film preparation for detection of Plasmodium spp. Data on the socio-demographic and clinical characteristics of the study participants were collected using an android technology software kobo-collect by interview. Results Of the total number of patients aged 2-37 years (median age = 6 years, IQR 3-11), 82 (52.2%) were females. The proportion of febrile patients with falciparum malaria was 57/157 (36.3%), while Salmonella typhi O and H antigens were detected in 23/157 (14.6%) of the samples. The detection rate of Salmonella spp in febrile patients was 10/157 (6.4%). Malaria and typhoid fever coinfection using Widal test and blood culture was 9 (5.7%) and 3 (1.9%), respectively. The isolates were highly susceptible to cefotaxime, ceftriaxone, ciprofloxacin, and amikacin but resistant to ampicillin, tetracycline, co-trimoxazole, gentamicin, cefuroxime, chloramphenicol, and meropenem. Conclusion Plasmodium falciparum and Salmonella spp coinfections were only up to 1.9%, while malaria and typhoid fever, individually, were responsible for 36.3% and 6.4%, respectively. Treatment of febrile conditions must be based on laboratory findings in order not to expose patients to unnecessary side effects of antibiotics and reduce the emergence and spread of drug resistance against antibiotics.